2019
DOI: 10.3390/md17030148
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Thin-Layer Chromatography Hyphenated with Microchemical and Biochemical Derivatizations in Bioactivity Profiling of Marine Species

Abstract: Marine organisms produce an array of biologically active natural products, many of which have unique structures that have not been found in terrestrial organisms. Hence, marine algae provide a unique source of bioactive compounds. The present study investigated 19 marine algae and one seagrass collected from Torquay beach, Victoria, Australia. High-performance thin-layer chromatography (HPTLC) hyphenated with microchemical (DPPH•, p-anisaldehyde, and Fast Blue B) and biochemical (α-amylase and acetylcholine es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 41 publications
0
12
0
2
Order By: Relevance
“…The ethyl acetate extract from nonfermented dried leaves was compared with ethyl acetate extracts from fermented dried and fermented fresh rosemary leaves, in terms of antioxidant activity, total phenolic content, and extraction of natural products, via HPTLC screening analysis. Ethyl acetate was selected as the most efficient solvent for extraction of the widest range of polyphenolics and phytosterols [ 19 ]. It is a moderately polar solvent that has the advantages of being volatile, relatively non-toxic, and non-hygroscopic.…”
Section: Resultsmentioning
confidence: 99%
“…The ethyl acetate extract from nonfermented dried leaves was compared with ethyl acetate extracts from fermented dried and fermented fresh rosemary leaves, in terms of antioxidant activity, total phenolic content, and extraction of natural products, via HPTLC screening analysis. Ethyl acetate was selected as the most efficient solvent for extraction of the widest range of polyphenolics and phytosterols [ 19 ]. It is a moderately polar solvent that has the advantages of being volatile, relatively non-toxic, and non-hygroscopic.…”
Section: Resultsmentioning
confidence: 99%
“…The latest α-amylase inhibition method, which used immersion of the plate into enzyme and substrate solutions ( Agatonovic-Kustrin and Morton, 2017 ; Agatonovic-Kustrin et al, 2019 ), was adjusted and transferred to a piezoelectric spraying procedure, in which the enzyme solution (62.5 U/mL in sodium acetate buffer) was sprayed onto the chromatogram (1 ml, red nozzle, level 5), followed by 30 min incubation at 37°C. As substrate 2%-soluble starch solution was sprayed onto the wet plate (0.5 ml, red nozzle, level 5).…”
Section: Methodsmentioning
confidence: 99%
“…This spot was visualized yellow or blue-violet when sprayed with KMnO4 or with p-anisaldehyde/ sulfuric acid stainning solutions, respectively implying the triterpene nature of the spot. [11] This observation was supported by its 1 H and 13 Silica gel column chromatography eluted by different solvents failed to separate these triterpenes. However, literature showed that by changing the functional groups, the polarity of these compounds could be altered.…”
Section: Resultsmentioning
confidence: 87%